The efficacy of citalopram in the treatment of premature ejaculation: a placebo-controlled study - Atmaca, M; Kuloglu, M; Tezcan, E; Semercioz, A (Springernature, 2002)
Background: Despite the limited number of available study comparing of their efficacy, selective serotonin re-uptake inhibitors (SSRI) have been thought to have beneficial effects for the patients with premature ejaculation. In the present study, we decided to examine the efficacy of citalopram, an SSRI, in the treatment of premature ejaculation. Method: The study was consisted of 26 married patients diagnosed with premature ejaculation according to Diagnostic and Statistical Manual of Mental Disorders Third Revised Version (DSM-III-R). The patients were randomly assigned to two groups, citalopram (group I) and placebo (group 11), each consisting of 13 patients. The effects of drug on the ejaculatory function were assessed by the intravaginal ejaculation latency time. Additionally, all patients were screened by using Clinical Global Impression-Improvement Scale (CGI-I) and Yonsei Sexual Function Inventory-II (YSFI-II). Results: The increase in the intravaginal ejaculation latency time in the citalopram group was statistically significant than that of placebo group. In addition, with respect to the subscales of the YSFI-II scale, similar overall significant improvements were seen in the patients given citalopram compared to those given placebo. Of group I patients, five (38.5%) were considered as 'very much improved' and four (30.8%) 'much improved' by CGI-I and only one of group 11 patients (7.7%) showed 'much improved'. Conclusion: The patients treated with citalopram showed significantly greater improvement compared to the patients receiving placebo.
Keywords: SSRI; citalopram; placebo; premature ejaculation